Властивості взаємоспектральних густин періодично нестаціонарних вібраційних сигналів - Яворський, І.М.; Кравець, І.Б.; Мацько, І.Й. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The cross spectral density properties of periodically correlated random processes stationary components are analyzed. Their representation throw the auto- and crosscorrelation functions of quadrature components is considered. The formula for coherent function is concretized.